MANNHEIMIOSIS IN GOATS AND SHEEP - O. Yu. Chernykh; A. A. Shevchenko; V. A. Mishchenko; A. V. Mishchenko; L. V. Shevchenko; A. V. Toropyno; A. Yu. Manakova (Ветеринарная патология, 2022)
The article presents the analysis results of sheep’s and goats’ examinations, care and feeding conditions at various farms of the Krasnodar Region unfavourable in terms of the upper respiratory tract infectious diseases. The sick animals clinical study data, the pathoanatomical changes found at autopsy on dead small ruminants, the laboratory research results have been noted. The clinical signs in sick goats and sheep were manifested by fever, cough, flux of mucous exudate from the nose. At autopsy on dead animals the lobular fibrinous bronchopneumonia with coagulative necrosis, the fibrinous pleurisy were found; the exudate in the alveolar tissue of the lungs and edema were detected, and when cut, a marble appearance of the lungs. The causative agent Mannheimia haemolytica was isolated from the pathological material taken from corpses of dead goats and sheep. Upon the analysis of examinations it was proved that in case of viral infections the efficiency of the respiratory system defence mechanisms weaken, causing colonisation by microbes of Mannheimia haemolytica species. The Mannheimia haemolytica microorganism in ruminants is nasopharynx and upper respiratory system commensal. Under normal conditions the Mannheimia haemolytica microorganism might not always cause the infectious disease in small cattle. The occurrence of this disease at the farms depends on the presence of various predisposing factors related to the deterioration of feeding and care conditions. All this confirms that mannheimiosis is a factorial disease.